2021
DOI: 10.1017/xps.2020.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Neighbor-to-Neighbor Get-Out-the-Vote Program: Evidence from the 2017 Virginia State Elections

Abstract: We analyze the results of a neighbor-to-neighbor, grassroots get-out-the-vote (GOTV) drive in Virginia, in which unpaid volunteers were encouraged to contact at least three nearby registered voters who were likely co-partisans yet relatively unlikely to vote in the 2017 state election. To measure the campaign’s effectiveness, we used a pairwise randomization design whereby each volunteer was assigned to one randomly selected member of the most geographically proximate pair of voters. Because some volunteers un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The racial composition of one's neighborhood is a powerful determinant of how individuals perceive the space around them (Wong 2010), influencing residential sorting, neighborhood trust, exclusionary attitudes, and group conflict (Enos 2017;Massey and Denton 1993). Likewise, Democrats and Republicans are increasingly likely to live separate from one another (Brown and Enos 2021;Rodden 2019), and this partisan homogeneity influences political attitudes and behaviors (Handan-Nader et al 2021;Perez-Truglia 2017). As such, when people consider their neighborhood or local community, they may define it along racial dimensions.…”
Section: Empirical Applicationsmentioning
confidence: 99%
“…The racial composition of one's neighborhood is a powerful determinant of how individuals perceive the space around them (Wong 2010), influencing residential sorting, neighborhood trust, exclusionary attitudes, and group conflict (Enos 2017;Massey and Denton 1993). Likewise, Democrats and Republicans are increasingly likely to live separate from one another (Brown and Enos 2021;Rodden 2019), and this partisan homogeneity influences political attitudes and behaviors (Handan-Nader et al 2021;Perez-Truglia 2017). As such, when people consider their neighborhood or local community, they may define it along racial dimensions.…”
Section: Empirical Applicationsmentioning
confidence: 99%
“…The paper, which examined 84,000 state legislative candidates from 1992 to 2020, found that polarization in state legislatures has been substantially increasing over recent decades with more extreme candidates enjoying electoral advantages previously experienced by more moderate candidates. This has national implications since the majority of sitting congress members were previously state legislators (Handan-Nader, Meyers, & Hall, 2022).…”
Section: Introductionmentioning
confidence: 99%